Study protocol: the INTERMAP China Prospective (ICP) study - Yan,L; Carter,E; Fu,Y; Guo,D; Huang,P; Xie,G; Xie,W; Zhu,Y; Kelly,F; Elliott,P; Zhao,L; Yang,X; et al. (Wellcome Open Research, 2020)
Background: Unfavourable blood pressure (BP) level is an established risk factor for cardiovascular diseases (CVD), while the exact underlying reasons for unfavourable BP are poorly understood. The INTERMAP China Prospective (ICP) Study is a prospective cohort to investigate the relationship of environmental and nutritional risk factors with key indicators of vascular function (BP, arterial stiffness, carotid-intima media thickness) among middle-aged/older men and women.Methods: A total of 839 Chinese participants aged 40-59 years from three diverse regions of China were enrolled in INTERMAP in 1997/98; data collection included repeated BP measurements, 24-hour urine specimens, and 24-hour dietary recalls. In 2015/16, 574 of these 839 persons were re-enrolled along with 208 new participants aged 40-59 years that were randomly selected from the same study villages. Participant’s environmental and dietary exposures and health outcomes were assessed in this open cohort study, including BP, 24-hour dietary recalls, personal exposures to air pollution, grip strength, arterial stiffness, carotid-media thickness and plaques, cognitive function, and sleep patterns. Serum and plasma specimens were collected with 24-hour urine specimens. A follow-up visit has been scheduled for 2020-2021.Discussion: Winter and summer assessments of a comprehensive set of vascular indicators and their environmental and nutritional risk factors were conducted with high precision. We will leverage advances in exposome research to identify biomarkers of exposure to environmental and nutritional risk factors and improve our understanding of the mechanisms and pathways of their hazardous cardiovascular effects. The ICP Study is observational by design, thus subject to several biases including selection bias (e.g., loss to follow-up), information bias (e.g., measurement error), and confounding that we sought to mitigate through our study design and measurements. However, extensive effo